Kalimat Interogatif dalam Kanal YouTube ‘ChinesePod’: Kajian Sintaksis - Wulan Sekar Arum; Puspa Mirani Kadir; Wagiati Wagiati (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
Interrogative sentences are an important aspect of learning a foreign language. Research on Chinese interrogative sentences is still very rare, so the writer chooses to research Chinese interrogative sentences. This study aims to examine the interrogative sentences contained in the video entitled '旅行在中国 Traveling in China' on the YouTube channel 'ChinesePod'. This research is a qualitative descriptive study, using observation and note-taking techniques. The data is classified based on the type of interrogative sentence, the function and location of the question word in each interrogative sentence. The results obtained show that there are 10 types of questions with 'yes/no' answers with ten question words functioning as predicates. Then there are 7 types of questions with answers to information which are divided into three question words which function as subjects, two question words function as predicates, one question word functions as a delimiter, and one question word functions as an adverb of place.Keywords – Chinese, Interrogative Sentence, Syntax.